Australian shepherds - Hansen, Grace (Abdo Kids, 2021)
This title introduces readers to the beautiful and talented Australian shepherd breed. The book talks about what the dogs look like, their talents, common personality traits and needs. Young readers will love the simple, easy-to-read text and beautiful full-color photographs.